BUILDING THE MORALS OF THE NATION'S CHILDREN FOR INDONESIA - Murtalitas; Aziz, Mursal (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2023)
Building the morals of the nation's children is the main responsibility of integrated Islamic education. Education that instills faith, morals, intelligence and aesthetics based on the development of the child's soul. Here, collective awareness of Muslims is needed. This means that assessing joint strategies to build the morals of the people and nation is a necessity. The regeneration of monotheism, devotion to worship, noble character and high knowledge are the internal demands and challenges of Muslims. Islamic education needs to start from teaching monotheism to deepen faith, improve morals, strengthen worship, expand mu'amalah for the glory of Muslims as the best people (khaira ummah), who move on the middle/fair path (ummatan washotan), and in the unity of monotheism.